PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER KEDISIPLINAN SISWA DI SMK PGRI 3 MALANG - Saraskia Mei Choirunnisa; Muhammad Afifulloh; Adi Sudrajat (VICRATINA, 2020)
This0study aims0to0determine0the role of0teachers activity of students0in disciplinary activities in learning at school. The0problem0faced is0that there0are still many0students who0have not been0able to apply the character of the discipline that has been taught by teachers, especially Islamic religious education teachers well. Evidently there are still many students who are still late coming to school, there are clothes that are not neat, sometimes in class there are students who joke around, eat, and fall asleep. Data0sources were0obtained from0the principal, teachers and0some0students. The0results of this0study0indicate that the development0of teachers in0shaping the character0of0students is good, only from within students who are sometimes less aware that behaving discipline is important. Teachers usually0create sects to0discuss matters0about0religion so students0get0a0strong Islamic character in0themselves.